SARS-CoV-2 Vaccination in Children and Adolescents—A Joint Statement of the European Academy of Paediatrics and the European Confederation for Primary Care Paediatricians - Dembiński, Łukasz; Vieira Martins, Miguel; Huss, Gottfried; Grossman, Zachi; Barak, Shimon; Magendie, Christine; del Torso, Stefano; Dornbusch, Hans Jürgen; Mazur, Artur; Albrecht, Katarzyna; Hadjipanayis, Adamos (Frontiers in Pediatrics, 2021)
Stopping the COVID-19 pandemic and its socio-economic consequences is only possible with a multifaceted strategy, including mass vaccination. Studies have been conducted mainly in adults, and data on the pediatric population is relatively limited. However, it appears that vaccination in children and adolescents is highly effective and safe. Despite the apparent benefits of vaccinating this age group, there are some medical and ethical concerns. Based on the above considerations, the European Academy of Paediatrics (EAP) and the European Confederation of Primary Care Pediatricians (ECPCP) assessed the current situation and presented recommendations for international and national authorities, pediatricians, and pediatric societies regarding vaccination against SARS-CoV-2 in children and adolescents.